Investigating the Relationship between Children, Depression, and Pain in Black Women with Sickle Cell Disease (SCD) - Tracey V. Hawkins; Mary Wood; Goldie S. Byrd; Ashland Thompson; Elwood Robinson; Camela S. Barker; Labarron Hill; Andrea Hobkirk; Keith E. Whitfield; Sandy Waters; Dwayne Brandon; Les Brinson; et al. (Journal of Hematology and Oncology Research, 2014)
Medical advances in obstetrics and hematology have encouraged researchers to investigate the reproductive risk in women with Sickle Cell Disease (SCD) attempting motherhood. However, few hematological studies have been completed focused specifically on the reproductive mental health of Black women with SCD. Historically women with SCD have been guided away from childbirth under the premise that they were not emotionally or physically capable of managing children. One question that remains unclear, from the limited research available in this area, is whether the presence of children serves to influence mood and pain in Black women with SCD. The current study examined the effects of the presence of children on self-reported pain and depressive symptoms and the relationship between pain and psychological functioning in African American women with SCD. Self-reported rates of depression, pain intensity, and pain severity were evaluated in 70 African American females with SCD. Results of Analysis of Covariance (ANCOVA) did not find differences in reported mood or pain between women with and without children. The current study serves as an initial observation upon which replication of the current findings and future prospective studies can be conducted. The study may ultimately mature into an area of research that guides reproductive decision-making for women with SCD and their doctors.
Keywords: Sickle Cell Disease